Architecture, Science Fiction and Re-imagining an Alternative Future - Nic Clear (Architecture Image Studies Scientific Journal)
This introductory essay argues that we are in a period of great change initiated by the intersection of three great challenges: climate catastrophe, technological convergence and the need for social justice. The response to the current Covid pandemic suggests that we are poorly prepared to face such transformations and may struggle to find appropriate solutions in the face of fear and resistance to the unknown. A central role for the arts in setting a progressive agenda will be in the communication of alternatives and perhaps by turning to forms of speculative fiction, such as SF, we will able to embody possible solutions into more tangible forms and encourage greater acceptance of the radical decisions that society undoubtedly needs to make.